Optimalisasi Proses Pengiriman Barang Pada PT. Surya Alam Maju Perkasa Untuk Meningkatkan Kepuasan Pelanggan - Novita Ekasari; Aji Nurfaizi Alhafidz (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2025)
The  development of digital technology has driven an increasing demand from society for information systems that are fast, efficient, and accurate. The report from the Indonesian Internet Service Providers Association (APJII) in 2025 shows that the internet penetration rate in Indonesia reached 80.66%, with 83.39% of users accessing the internet via mobile devices. This situation opens up significant opportunities for utilizing technology in business processes, including the logistics and goods delivery sector. PT Surya Alam Maju Perkasa, as a distributor company, still faces various obstacles in the delivery process due to the lack of a computerized information system. The manual systems used, such as recording delivery routes and reporting via instant messaging applications, lead to data inconsistencies, delivery delays, inefficient operational processes, and a high rate of undelivered items. Based on operational data from October 2025, there were 1,347 deliveries recorded with 69 cases of undelivered items. This research aims to design an integrated web-based goods delivery information system to enhance operational efficiency and minimize errors. This study is qualitative, involving direct observation and interviews with operation manager during October and November 2025. The development method used refers to the Software Development Life Cycle. The results indicate that the designed system can facilitate real-time monitoring of deliveries, accelerate the reporting process, and improve information accuracy. Web system and operating systems also offers flexibility for users. The implementation of this information system has the potential to improve the company's logistics performance, minimize the risk of undelivered goods, and enhance customer trust.